Hubungan Sikap pada Pelajaran Pendidikan Agama Kristen dengan Motivasi Belajar Siswa - Kristian Adi Santoso (KHARISMATA: Jurnal Teologi Pantekosta, 2025)
Learning motivation is a crucial determinant of academic achievement. However, in practice, not all students exhibit strong motivation, which can result in diminished academic performance. An individual's attitude toward a subject is known to influence behaviour in accordance with that attitude; a positive attitude typically leads to a positive behavioural response. In the context of education, students' attitudes toward a particular subject may affect their motivation to engage with it. Therefore, cultivating a positive attitude toward Christian Religious Education (CRE) is viewed as essential for improving student motivation and, in turn, learning outcomes. This study aims to analyse and empirically determine the relationship between students’ attitudes toward Christian Religious Education and their learning motivation. The research utilises a quantitative correlational design. A total of 76 students were selected from a population of 95 using the Krejcie and Morgan sampling table. Data were collected through a closed-ended questionnaire, with variables measured using a Likert scale. Hypothesis testing was conducted using simple linear regression and correlation analysis. The findings indicate a positive and statistically significant relationship between students’ attitudes toward Christian Religious Education and their learning motivation. These results suggest that enhanced attitudes toward the subject correspond with increased motivation, which is further reflected in students' academic behaviour and performance.   Motivasi belajar merupakan salah satu faktor penting untuk mencapai prestasi yang baik. Namun dalam kenyataannya adalah tidak semua siswa memiliki motivasi belajar yang baik, dan hasilnya dapat dipastikan prestasinya juga akan kurang baik. Sikap seseorang terhadap sesuatu dapat berpengaruh terhadap perilaku sesuai dengan sikap tersebut. Jika sikapnya positif maka responnya juga akan positif. Jika dikaitkan dengan motivasi belajar, maka sikap terhadap mata pelajaran akan memengaruhi motivasi belajar siswa. Sehingga untuk meningkatkan motivasi belajar siswa, perlu peningkatan sikap positif terhadap pelajaran pendidikan agama kristen, yang akan berdampak pada peningkatan hasil belajar siswa. Tujuan penelitian ini adalah untuk menganalisis dan membuktikan apakah terdapat hubungan Sikap pada mata pelajaran pendidikan agama kristen dengan motivasi belajar siswa. Penelitian ini menggunakan metode kuantitatif korelasional. Responden sebanyak 76 siswa dari 95 siswa berdasarkan tabel Krejcie Morgan. Instrumen yang digunakan adalah kuesioner tertutup dan penilaian pada setiap variabel dengan skala Likert. Analisis uji hipotesis dengan menggunakan regresi sederhana dan korelasi. Hasil penelitian ini menunjukkan bahwa terdapat hubungan yang positif dan signifikan sikap pada pelajaran pendidikan agama kristen dengan motivasi belajar siswa.  Hasil tersebut memberi makna bahwa apabila sikap pada pelajaran pendidikan agama Kristen meningkat maka motivasi belajarnya juga meningkat, yang dicerminkan pada perilaku dan hasil belajar siswa.